The Robotics Divide A New Frontier in the 21st Century? - López Peláez, Antonio (Springer London : Imprint: Springer, 2014)
Societies survive in their environment and compete with each other depending on the technology they develop. Economic, military and political power are directly related to the available technology, while access to technology is key to the well-being of our societies at the individual, community and national level. The Robotics Divide analyzes how robotics will shape our societies in the twenty-first century; a time when industrial and service robotics, particularly for military and aerospace purposes, will become an essential technology. The book, written by experts in the field, focuses on the main technological trends in the field of robotics, and the impact that robotics will have on different facets of social life. By doing so, the authors aim to open the â_oblack boxâ__ of a technology which, like any other, is designed, implemented and evaluated according to the economic and cultural patterns of a cosmopolitan society, as well as its relations of power. The Robotics Divide explores future developments in robotics technology and discusses the model of technological development and the implementation of robotics in this competitive market economy. Then the authors examine to what extent it is possible to determine the characteristic features of the robotic divide, namely in what ways the robotic divide differs from the digital divide, and how a model to integrate this technology can be developed without reproducing patterns of inequality and power that have characterized the advent of previous technologies. These issues - inequality, robotics and power - are of concern to robotics and advanced automation engineers, social scientists, economists and science policy experts alike.